(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the theoretical and methodological foundations of studying the formation of egoistic thinking in the context of globalization, the philosophical and conceptual analysis of the formation of egoistic thinking in the context of globalization, and the prospects for developing the motivation of altruism against egoistic thinking in the context of globalization. The article studies the philosophical and conceptual analysis of the formation of egoistic thinking in the context of globalization.